Niche-Relationships Within and Among Intertidal Reef Fish Species - Andrades, Ryan; Joyeux, Jean-Christophe; Macieira, Raphael M.; Godoy, Bruno Spacek; Reis-Filho, José Amorim; Jackson, Andrew L.; Giarrizzo, Tommaso (Frontiers in Marine Science, 2021)
Niche-related processes (e.g., density or niche-breadth compensation and competition) are fundamental to a broad understanding of community ecology and ecosystem functioning. Most evidences of competition are from controlled indoor trials with few species, and it remains a challenge to estimate competition among multiple species in the field. Here, we analyze stable isotopes and distributional data from 51 fish taxa in six locations in the southwestern Atlantic to predict intraspecific trophic pressure (ITP) and the potential competitive strength among species in a trophic-based framework. We used two proxies built upon 2-dimensional isotopic space (δ13C vs. δ15N), its predicted overlap, and fish density to calculate winner and loser taxa in potential paired interspecific competitive interactions. The intraspecific proxy indicated that cryptobenthic fishes are under high among-individual trophic pressure (high densities and small niche sizes). Also, cryptobenthic behavior together with feeding specialization and extremely small-sizes were the most important traits related to low success in interspecific simulations. Although cryptobenthic fishes face strong competitive pressures, there are some known inherent trade-offs to cryptobenthic life such as trophic and habitat use specializations. These seem to compensate and ensure coexistence among cryptobenthic fishes and non-cryptobenthic species. Habitat loss/degradation via urbanization, invasive species and climate-change-driven sea-level rise can reduce the suitability of habitat and increase competition on cryptobenthic species, especially in shallow reefs and intertidal shores.